(untitled) - Lipsky, David (New York, 2004)
As David Lipsky follows a future generation of army officers from their proving grounds to their barracks, he reveals the range of emotions and desires that propels these men and women forward...
Keywords: English language,Ngôn ngữ Anh; Study and teaching,Học và dạy